The Landscape Design Proposal for the New Archeological Museum of Cyprus - Julia Nerantzia Tzortzi (Land, 2024)
This paper deals with the landscape design strategy that was followed in the proposal that was submitted to the International Architecture Competition of the New Archaeological Museum of Cyprus. The aim of this document is to analyze how landscape and architecture interact. In the author’s design proposal for the New Archaeological Museum of Cyprus, the various “gardens” integrated into the Landscape are analyzed. The concept of landscape design is related to the sacredness of trees to certain gods in Ancient Greece and Greek Mythology. The proposal addresses the symbolic meaning of trees and water. The design triggered the creation of several “gardens”: the “Sacred Garden”, the “Stone Garden”, the “Olive Garden”, the “Sacred Grove”, and the “Public Garden”, combining their soft landscapes with the hard landscape of the “Plaza” and the “Courtyard”. Each figure in the garden has a symbolic meaning that allows for a dialogue between landscape and architectural design. In addition, the findings provide valuable insights into the historical and spiritual value of landscape elements (plants, water) that are also thermal regulators for sustainable urban planning. The research results may be of value to landscape architects, architects, and landscape designers in the Mediterranean region.